Implementasi Metode An-Nashr Untuk Meningkatkan Kemampuan Menghafal Terjemah Ayat Al-Quran Pada Siswa Madrasah Tsanawiyah - Aliyah, Nasichatul; Nikmah, Faridatun (J-PAI: Jurnal Pendidikan Agama Islam, 2022)
The An-Nashr method is a program owned by NU Pakis Islamic Junior High School to facilitate the students in learning to read Al-Quran properly and correctly while understanding the meaning contained in it by memorizing the Al-Qur'an verses translation. This research aimed to describe the implementation of the An-Nasr Method to improve the memorizing ability of Al-Quran verses translation of NU Pakis Islamic Junior High School Students. This research used a descriptive qualitative approach. The results of this research: 1) Implementation of the an-nasr method to improve the memorizing ability of Al-Quran verses translation of NU Pakis Islamic Junior High School Students through several processes, namely planning and implementation. In planning, an initial test is carried out on students which aims to facilitate class grouping based on students' ability to read Al-Quran. Then in its implementation, it follows the An-Nashr method manual in the learning process. 2) The improvement of students' ability to memorize the translation of Al-Quran verses can be seen from the student learning journal notes. 3) Learning Evaluation of the an-nasr method implementation can be done by means of an assessment of student memorization, a warning to a supervising teacher.